Analysis Of Strategic Entrepreneurship To Increase The Export Of Micro, Small, And Medium Enterprises (MSMEs) In Indonesia: A Case Study Of Java Halu Coffee - Dindin Abdurohim; Andry Mochamad Ramdan (Pusat Riset dan Inovasi Nasional, 2023)
Strategic Entrepreneurship, also known as entrepreneurial strategy, serves as a pathway for SMEs to enter the international market smoothly. When SME products enter the international market, it is essential for companies to devise entrepreneurial strategies in marketing to increase sales volume and generate profits.Coffee is a prominent commodity in West Java due to its mountainous terrain, which provides favorable conditions for coffee cultivation. Java Halu Coffee, located in Bandung Barat Regency, West Java, is one of the SMEs in the coffee bean and coffee processing industry.The objective of this research is to describe the entrepreneurial strategies employed by Java Halu Coffee in entering and marketing its products in the international market. The study also explores the application of entrepreneurial strategies in increasing the export volume of coffee beans and alternative strategies.This research utilizes a descriptive qualitative approach. The primary data sources consist of interviews conducted with the owner of Java Halu Coffee, while secondary data sources include relevant documents related to the research theme.The research findings indicate that Java Halu Coffee has chosen export as its entry strategy into the international market. The company implements growth, innovation, network, and harvest/exit strategies. This includes identifying market development opportunities, innovating its products, establishing good relationships with buyers, forming beneficial networks, and collaborating with similar companies to meet market demands. These strategies enable Java Halu Coffee to maximize sales and increase the export volume.